THE NEEDS ASSESSMENT FOR DEVELOPING THE MEASUREMENT AND EVALUATION OF LEARNING COMPETENCY USING STUDENT CENTERED IN OPPORTUNITY EXPANSION SCHOOL OF RAYONG PROVINCE - Sohsiri, Massaya; Jiraro, Pongthep; Khawloueng, Dusit (Academic Journal of Thailand National Sports University, 2019)
The purposes of this research were: 1) to study current situation of developing the measurement and evaluation of learning competency using student centered, 2) to compare and study the relationship of the measurement and evaluation of learning competency using student centered in the past, 3) to evaluate the needs assessment for developing measurement and evaluation of learning competency using student centered. The samples of this research were 276 teachers in opportunity expansion schools in Rayong province, selected by the multistage sampling. The instruments for collecting the data were the rating-scale and open-ended questionnaire. The statistics for analyzing the data were percentage, mean, standard deviation. In addition, researcher compared and tested the difference of mean with t-test and One-way ANOVA, Scheffe’s test and Pearson correlation method. Research results were that: 1) teachers had the measurement and evaluation of learning competency using student centered at a moderate level; 2) The practice of the measurement and evaluation with different ages, educational background and field were statistically significant different at 0.05 level, on the other hand, the teachers’ age and teaching experiences were not statistically significant correlations with the performance of measurement and evaluation; 3) The need assessment results were that measurement came first followed by collecting data of the measurement and evaluation, determining the purpose of measurement and evaluation, reporting and applying, and using methods and tools to measure and evaluate, respectively